Germinação de sementes de romäzeiras (Punica granatum L.) de acordo com a concentração de giberelina - Takata, William [UNESP]; Silva, Ewerton Gasparetto Da [UNESP]; Corsato, Jaqueline Malagutti; Ferreira, Gisela [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The pomegranate (Punica granatum L.) fruit tree is shrubby, often used as an ornamental plant and operated as its medicinal characteristics. Its fruits have internal cavities that host numerous seeds and without the presence of endosperm. These seeds are germinating some difficulty, and it was possible to achieve satisfactory percentages of germination using laminating process that is required for breaking of physiological dormancy, as alters hormone balance, particularly gibberellin levels. The study aimed to evaluate the application of GA3 concentrations on germination of seeds of Punica granatum in controlled temperature of 25ºC and a photoperiod of 12 hours of light on paper germitest environment. We adopted the completely randomized design, with five treatments [GA3 concentrations (0, 100, 200, 300 and 400 mg L-1)], four replicates of 25 seeds each. It was determined during the acquisition curve imbibition of water from the same. The variables evaluated were germination percentage, mean germination time, germination velocity index, index of synchronization and frequency of germination, total length (shoot + root), fresh weight and dry weight of seedlings. The only variable that showed the effect of concentrations of GA3 was the emergence rate index. The soaking time required to achieve maximum water content in the seeds of pomegranate tree (P. granatum) in deionized water was four hours, this soaking liquid effective method for the germination process, without the need to Gibberellin.

A romäzeira (Punica granatum L.) é fruteira de porte arbustivo, utilizada geralmente como planta ornamental e explorada quanto a suas características medicinais. Seus frutos apresentam cavidades internas onde estäo alojadas numerosas sementes e sem a presença de endosperma. Estas sementes apresentam certa dificuldade para germinar, sendo que se conseguiu atingir porcentagens satisfatórias de germinação com a utilização de estratificação, que é processo necessário para a quebra da dormência fisiológica, já que altera o balanço hormonal, sobretudo os níveis de giberelina. O trabalho teve por objetivo avaliar a aplicação de concentrações de GA3 na germinação de sementes de Punica granatum em ambiente controlado com temperatura de 25ºC e fotoperíodo de 12 horas de luz, sobre papel germitest. Adotou-se o delineamento inteiramente casualisado, com cinco tratamentos [concentrações de GA3 (0; 100; 200; 300 e 400 mgL-1)], quatro repetições de 25 sementes cada. Determinou-se durante a embebição a curva de aquisição de água das mesmas. As variáveis avaliadas foram porcentagem de germinação, tempo médio de germinação, índice de velocidade de germinação, índice de sincronização e frequência de germinação, comprimento médio total (parte aérea + parte radicular), massa da matéria fresca e seca das plântulas. A única variável que mostrou efeito das concentrações de GA3 foi o índice de velocidade de emergência. O tempo de embebição necessário para atingir máximo teor de água nas sementes de romäzeira (P.granatum) em água deionizada foi de quatro horas, sendo a embebição neste líquido o método eficaz para o processo germinativo, sem a necessidade de uso de giberelina.
Germinat ion of pomegranate (Punica granatum L.) seeds under giberellin concentrations
Keywords: Romä; regulador vegetal; giberelina; Pomegranate; plant growth regulator; gibberellin